PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO ) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN PERBANKAN PERIODE TAHUN 2012-2014 - Yayang Swasono, 14.05.51.0281; Sudarsi, Sri (Students Journal of Economic and Management, 2017)
The purpose of this research was to determine the effect of the Capital Adequacy Ratio (Car), Non Performing Loan (NPL), Operating Expenses and Operating Income (ROA) And Loan To Deposit Ratio (LDR) Of Return On Assets (ROA) The Banking Companies Period Year 2012-2014. Samples in this study is the overall financial statements of banks listed on the Indonesia Stock Exchange, ie from 2012 to 2014, amounting to 31 companies that meet the requirements to report financial data are complete. The analysis tool used is multiple linear regression. Results of research Capital Adequacy Ratio (CAR) negative effect on ROA. Non Performing Loan (NPL) a negative effect on ROA. Operating Expenses to Operating Income (ROA) but no significant negative effect on ROA and Loan to Deposit Ratio (LDR) to ROA. Keywords: CAR, NPLs, ROA, and LDR to ROA